Indonesia’s Traditional Knowledge Documentation in Intellectual Property Rights’ Perspective - Dwi Tiara Kurnilasari; Annalisa Yahanan; Rohani Abdul Rahim (Sriwijaya Law Review, 2018)
Indonesia is a fertile place for traditional knowledge with more than 300 ethnical group inhabitants. Therefore, it is not surprising to know that Indonesia has the enormous potential of tradi-tional knowledge. However, Indonesia is still has some problems in legal framework to protect it. The research applies doctrinal research method. The problems that will be discussed in this article is what type of traditional knowledge documentation system that used in Indonesia and how it is performed in order to protect traditional knowledge. There are few goals from this research which are to find out about Indonesia's traditional knowledge documentation system and to compare it with other countries that also use documentation as the protection method. As a result, traditional knowledge documenta-tion system used in Indonesia is external registries which are done by parties outside the indigenous communities (Government, Academist, and NGO) and the information about traditional knowledge is placed in public domain. Even though it has not perfectly documented like India's Traditional Knowl-edge Digital Library, Indonesia has documented few of its traditional knowledge such as Songket pat-tern that belongs to South Sumatera. It could be summarized that traditional knowledge documenta-tion has a vital role as one of the most practical methods to perform traditional knowledge protection. In order to protect traditional knowledge, these documented activities need to be enhanced so it could give the financial benefit to indigenous communities as its owner.